Semistrict -Preinvexity and Optimality in Nonlinear Programming - Z. Y. Peng; Z. Lin; X. B. Li (Abstract and Applied Analysis)
A class of semistrictly -preinvex functions and optimality in nonlinear programming are further discussed. Firstly, the relationships between semistrictly -preinvex functions and -preinvex functions are further discussed. Then, two interesting properties of semistrictly -preinvexity are given. Finally, two optimality results for nonlinear programming problems are obtained under the assumption of semistrict -preinvexity. The obtained results are new and different from the corresponding ones in the literature. Some examples are given to illustrate our results.